A COMPARISON OF METHODOLOGIES TO ASSESS BRIDGE CONDITION - Saraswati, Ayu; Thahir, Annisa Puji Lestari (SINERGI : Jurnal Riset Ilmiah, 2025)
Challenges such as corrosion and other deterioration phenomena can affect performance and disrupt bridge functionality. To address this need, a bridge management system is required to ensure optimal actions and strategies. Previous studies related to several condition assessment methods have been widely used, an in-depth review will be discussed in this paper. A comparison will be made to see the advantages and disadvantages. Three methods are reviewed and examined, the data used to determine the final condition is the result of visual inspection. BMS Indonesia uses a hierarchical system that still causes bias in its assessment. BHI uses condition state in its application, while BCR uses condition rating to determine the final value. BCR and BHI have advantages in assigning element importance weights, while BMS is good at considering each element's damage. Element importance weights are good to use in determining bridge condition values because they prioritize damage to crucial elements in the calculation. However, damage that occurs to supporting elements also needs to be considered because it can cause more serious damage if not treated further.